2020
DOI: 10.25081/jp.2020.v12.6324
|View full text |Cite
|
Sign up to set email alerts
|

Seed priming effects on germination and first growth of the medicinal plant Achillea millefolium L.

Abstract: This study evaluated the effects of seed priming on germination and growth of A. millefolium by means of laboratory and greenhouse experiments conducted during 2018 in the Agricultural University of Athens. Treatments were GA3 (400 and 800 ppm), potassium nitrate (2% and 4%), polyethylene-glycol (soaking for 12 and 24h) besides an untreated control. Experiment in Petri dishes revealed that GA3 at 400 ppm, potassium nitrate (at concentration 2 and 4%) and PEG significantly increased germination percenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
0
0
Order By: Relevance
“…The potassium component could have contributed to the activation of enzymes which are responsible for germination hence, the presence of KNO 3 resulted in the quickening of germination. The results in this study are also in line with the results found by Kanatas et al [28] in a study on Achillea millefolium L. Seed priming with potassium nitrate enhanced the germination rate. Results from this study also agree with Hoseini et al [29], whose study results showed that seeds primed with KNO 3 had the greatest observed germination rates.…”
Section: Effect Of Kno 3 On Germination Indices Of Horned Melonsupporting
confidence: 93%
See 1 more Smart Citation
“…The potassium component could have contributed to the activation of enzymes which are responsible for germination hence, the presence of KNO 3 resulted in the quickening of germination. The results in this study are also in line with the results found by Kanatas et al [28] in a study on Achillea millefolium L. Seed priming with potassium nitrate enhanced the germination rate. Results from this study also agree with Hoseini et al [29], whose study results showed that seeds primed with KNO 3 had the greatest observed germination rates.…”
Section: Effect Of Kno 3 On Germination Indices Of Horned Melonsupporting
confidence: 93%
“…The effect of KNO 3 on the dry weight of horned melon seedlings could be because of plant development due to the nitrogen in KNO 3, leading to more build-up of the plant biomass . Results from this study are in parity with the results obtained by Kanatas et al [28]. Earlier studies demonstrated that, the dry biomass of the seedlings was substantially increased after seed priming of Achillea millefolium L with KNO 3 The results of this study also are in agreement with the results obtained where seed priming increased the dry weight of soybean seedlings [48].…”
Section: Effect Of Kno 3 On Early Seedling Growth Of Horned Melonsupporting
confidence: 92%